If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1a + -2b) + -2(5b + -4a) = 0 (1a * -6 + -2b * -6) + -2(5b + -4a) = 0 (-6a + 12b) + -2(5b + -4a) = 0 Reorder the terms: -6a + 12b + -2(-4a + 5b) = 0 -6a + 12b + (-4a * -2 + 5b * -2) = 0 -6a + 12b + (8a + -10b) = 0 Reorder the terms: -6a + 8a + 12b + -10b = 0 Combine like terms: -6a + 8a = 2a 2a + 12b + -10b = 0 Combine like terms: 12b + -10b = 2b 2a + 2b = 0 Solving 2a + 2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 2a + 2b + -2b = 0 + -2b Combine like terms: 2b + -2b = 0 2a + 0 = 0 + -2b 2a = 0 + -2b Remove the zero: 2a = -2b Divide each side by '2'. a = -1b Simplifying a = -1b
| -.25x+6=.5x+3 | | y-35=4.7 | | 7x+7+5x+6= | | 4(x+2)-3x+5=x+5 | | x^2+18x=-32 | | 10x+7+4x+7= | | x^2=-169 | | 6x^2+18x^2= | | -2x+30=7(x+3) | | (2x-1)+2(3x+7)=6x-3 | | 12(1/6-2/3x)-20/3(-3/4) | | 2.458+45+16.29= | | 3w+5w=48 | | 5*p=40 | | 0.24=0.42 | | 3x-5+2=8 | | -x-3y=-32x+3y=5 | | -24=5(u-8)-7u | | -32+2y=-6y | | 2s=34 | | 3w(w)-(w-5)(w-3)=2w(w)+1 | | f-16=-32 | | 18-3x=-15 | | 45x+9y=63 | | 0.18x+0.2(x-3)=0.01(4x-1) | | X+12y=-40 | | (x+7)(x+7)=-14 | | 16.40=x-0.20*x | | 0.5P-10=50-P | | -8-7(r-6)=90 | | d=5m | | 2+5x=6x-8 |